В конце ноября: повесть / Т. Янссон ; пер. Н. Белякова ; худ. Т. Янссон - Янссон Туве (Друзья детства, 2007)
Экземпляры: ДБ (20120709) / Инвентарный номер: 40866zzzzz / Цена: 141.70 / Сис.шифр: 84(4Шве) / Авт.знак: Я 65 / ГРНТИ: 17.82.93 / ББК: 84(4Шве)